The Impact of Social Media on Mental Health and Well- Being on Students - Hasan, Mohammad Imtiaz; Akter, Tayeba (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This paper's goal was to examine how social media affects undergraduates' mental health and general well-being. Social media's pervasive usage in the contemporary digital era has fundamentally changed how individuals interact with one another. Although social media facilitates information exchange and social relationships, there are increasing concerns regarding its detrimental effects on mental health. The study examines previous research and literature and offers a thorough analysis based on various research findings, professional judgements, and long-term investigations. It begins by outlining social media's diverse applications and impacts. The impact of social media on fostering emotional experiences, self-esteem, and interpersonal interactions is then examined. This study examines social media's influence on mental health, both good and bad. Increased social support, community development, and opportunities to learn about mental health are all positive features. On the other hand, drawbacks include the possibility of addiction, excessive social comparison, and cyberbullying. Four questions were used to gather data, and a modified Likert scale was used for analysis to identify the social media sites that are most influencing students' lives.